2014
DOI: 10.1111/mec.12821
|View full text |Cite
|
Sign up to set email alerts
|

Plant host and soil origin influence fungal and bacterial assemblages in the roots of woody plants

Abstract: Microbial communities in plant roots provide critical links between above- and belowground processes in terrestrial ecosystems. Variation in root communities has been attributed to plant host effects and microbial host preferences, as well as to factors pertaining to soil conditions, microbial biogeography and the presence of viable microbial propagules. To address hypotheses regarding the influence of plant host and soil biogeography on root fungal and bacterial communities, we designed a trap-plant bioassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
189
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(215 citation statements)
references
References 73 publications
25
189
1
Order By: Relevance
“…In previous studies, the fungal community composition in roots was essentially analyzed either by cloning of PCR products (e.g., Vandenkoornhuyse et al, 2002a; Vandenkoornhuyse et al, 2002b) or more recently, by mass sequencing of amplicons using targeted DNA (e.g., Opik et al, 2013; Shakya et al, 2013a; Bonito et al, 2014). Others studies based on RNA and DNA extractions have used the RNA/DNA ratio as a proxy to investigate microbial dormancy and to estimate the metabolically active community (Aanderud et al, 2016; Jones & Lennon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the fungal community composition in roots was essentially analyzed either by cloning of PCR products (e.g., Vandenkoornhuyse et al, 2002a; Vandenkoornhuyse et al, 2002b) or more recently, by mass sequencing of amplicons using targeted DNA (e.g., Opik et al, 2013; Shakya et al, 2013a; Bonito et al, 2014). Others studies based on RNA and DNA extractions have used the RNA/DNA ratio as a proxy to investigate microbial dormancy and to estimate the metabolically active community (Aanderud et al, 2016; Jones & Lennon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also shown that phosphorus [9,12] and soil texture [13] can shape soil bacterial communities. The effects of abiotic parameters have been less often demonstrated in fungal communities [10,14]. Regarding biotic factors, several studies have clearly shown that aboveground plant cover influences the fungal community structure and the functional diversity of forest soils [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biotic factors, several studies have clearly shown that aboveground plant cover influences the fungal community structure and the functional diversity of forest soils [15–17]. However, plant community composition has little to no effect on bacterial communities [14,18]. Furthermore, soil bacteria and fungi have also been known to interact with each other.…”
Section: Introductionmentioning
confidence: 99%
“…(2 SAGs), Armatimonadetes sp., Acidobacteria sp., and Verrucomicrobia sp. that had previously been observed in microbiome studies of Populus endospheres (16–18) but that were not present in our culture collections from these systems.…”
Section: Resultsmentioning
confidence: 61%
“…These two compartments represent distinct environments for the growth of microbes. Both culture-independent and culture-dependent assessments of microbial communities from Populus have been undertaken, which includes community profiling using phylogenetic marker genes (16–18) and large culture collections of endosphere and rhizosphere isolates (19–21). The microbiome in these root-associated environments is comprised primarily of bacteria and fungi and, to a lesser extent, archaea which are virtually absent from the endosphere (18).…”
Section: Introductionmentioning
confidence: 99%